A system dynamics model for evaluating collaborative forest management: a case study in Indonesia - Purnomo, H.; Mendoza, G.A. (2011)
This article presents a system dynamics (SD) method to examine the problem of forest degradation. The model developed takes a system-oriented view of forest management, embracing both social and biophysical factors affecting deforestation. Social factors examined are socio-economic variables or elements that influence behaviour and decision-making choices at the household level. Biophysical factors are four sub-components that are considered major land uses namely, the paddy field component, rattan plantations, coffee plantations and forest stands. The model was applied in a case study located in Pasir District of East Kalimantan, Indonesia. The site covers an area that includes a protected forest and a privately allocated timber license concession. Three village communities are examined in the case study. The SD model developed was applied to the case study focusing on three management policies or scenarios, which are based on access rights to the forest resources within the study area. Specifically, the property arrangements examined in each scenario are: Policy 1 – status quo (i.e.continue present property rights arrangements); Policy 2 – local communities manage the forest exclusively; and Policy 3 – collaborative management involving both local communities and a private company. Results from the model show that the third policy is the most viable option, and also lead to a win–win solution.